First case of Mycobacterium heckeshornense cavitary lung disease in the Latin America and Caribbean region. (January 2016) - Coitinho, C.; Greif, G.; van Ingen, J.; Laserra, P.; Robello, C.; Rivas, C.
Abstract: A case of cavitary pulmonary disease caused by Mycobacterium heckeshornense in Uruguay is described. This is the first case reported in the Latin America and Caribbean region, showing that this species is a worldwide opportunistic human pathogen.